Senior Management Support Moderates the Influence of Auditor Characteristics on Internal Audit Effectiveness - Kurniawan, Rudy; Ikhsan, Syarbini; Cahya, Fuji Anggun Cahya (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2025)
This study aims to examine and analyze the influence of internal auditor integrity and moral courage on internal audit effectiveness, as well as to evaluate the moderating role of senior management support. The object of this research is internal auditors working at the BPKP Representative Office of West Kalimantan Province. The sample was determined using a census method involving 43 auditors. Primary data were collected through questionnaires. The analysis method used in this study is structural equation modelling (SEM) with a partial least squares (PLS) approach, processed using the warp-PLS 8.0 application. The novelty of this study lies in the use of warp-PLS, which is still rarely applied in internal audit research, and the specific focus on internal auditors at BPKP, a government institution with a strategic role in public sector supervision. The results show that internal auditor integrity and moral courage have a positive and significant effect on internal audit effectiveness. Furthermore, senior management support is proven to strengthen the connection between individual auditor characteristics and audit effectiveness. This research highlights the importance of integrity, moral courage, and organizational support in building an effective and accountable internal control system, especially within the public sector. Abstrak - Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh integritas auditor internal dan keberanian moral terhadap efektivitas audit internal, serta melihat peran dukungan manajemen senior sebagai variabel moderasi. Objek dalam penelitian ini adalah auditor internal yang bekerja di BPKP Perwakilan Provinsi Kalimantan Barat. Sampel diperoleh dengan teknik sensus terhadap 43 auditor. Data primer dikumpulkan melalui penyebaran kuesioner. Metode analisis yang digunakan dalam penelitian ini adalah structural equation modeling (SEM) dengan pendekatan partial least squares yang diolah menggunakan aplikasi warp-PLS 8.0. Penggunaan aplikasi warp-PLS dan fokus objek pada auditor internal di lingkungan BPKP merupakan novelty dalam penelitian ini, karena penelitian sebelumnya umumnya menggunakan SPSS atau smart-PLS dan belum banyak mengkaji konteks BPKP. Hasil penelitian menunjukkan bahwa integritas auditor internal dan keberanian moral berpengaruh positif dan signifikan terhadap efektivitas audit internal. Selain itu, dukungan manajemen senior terbukti memperkuat hubungan antara karakteristik individu auditor dengan efektivitas audit. Penelitian ini menegaskan pentingnya nilai integritas, keberanian moral, dan dukungan organisasi dalam menciptakan sistem pengawasan internal yang efektif dan akuntabel, terutama di sektor publik.